2012
DOI: 10.1039/c2jm34773c
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive organic near-infrared phototransistors based on poly(3-hexylthiophene) and PbS quantum dots

Abstract: Highly sensitive near-infrared (NIR) phototransistors based on poly(3-hexylthiophene) (P3HT) and lead sulfide quantum dots (PbS QDs) were fabricated by a solution process. The phototransistors show high responsivity up to 2 Â 10 4 A W À1 under NIR illumination with wavelength of 895 nm, which is much bigger than that of the photodetectors based on PbS QDs or organic semiconductors only. The sensing mechanism is attributed to the photo-induced electrons generated in the PbS QDs, which increase the threshold vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
67
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 36 publications
(60 reference statements)
3
67
2
Order By: Relevance
“…The separation of light absorption and field-effect charge transport effectively expands the selection of light sensitizers and consequently offers great potential for broadband or long wavelength light detection. [164] A maximum R of 2 × 10 4 A W −1 is obtained at 895 nm. [44] Peng et al adopted an organic small molecule sensitizer layer on top of CuPc phototransistors.…”
Section: Hybrid Phototransistormentioning
confidence: 91%
“…The separation of light absorption and field-effect charge transport effectively expands the selection of light sensitizers and consequently offers great potential for broadband or long wavelength light detection. [164] A maximum R of 2 × 10 4 A W −1 is obtained at 895 nm. [44] Peng et al adopted an organic small molecule sensitizer layer on top of CuPc phototransistors.…”
Section: Hybrid Phototransistormentioning
confidence: 91%
“…Similar phenomena have also been observed in organic semiconductors and PbS QD blend device. 44 Figure 3e shows the maximum values of R (R max ) as a function of the illumination wavelength in the spectral region of 1400-700 nm, which range between 670 and 3600 A W −1 . These values are comparable to or even better than the values of the PbS QD-based NIR photodetecting devices 8 or the 2D nanosheet-based phototransistors 45,46 previously reported in the literature.…”
Section: Phototransistor Characteristicsmentioning
confidence: 99%
“…Under 100 V bias, NIR photoresponsivity was as high as 10 4 A/W. 13 Yan's group and Konstantato et al both reported LH-FEpTs based on a graphene and PbS colloidal QD hybrid with ultrahigh responsivity of 10 7 A/W. 14,15 Theoretically, the responsivity (R ph ) of a thin film photoconductor is expressed as R ph ¼ enlEW/P, where e is the electronic charge, n is the photo-induced carrier density per unit area, l is carrier mobility, E is the applied electric field, P is the incident optical power, and W is the device width.…”
mentioning
confidence: 99%
“…Both types of FEpT show decreasing channel current with increasing light irradiation due to the light-gate effect. 13,14,21 The physical light-sensing mechanism is described as follows. Under illumination, photo-induced excitons are generated in the PbS QDs.…”
mentioning
confidence: 99%